Mark report satellite tags (mrPATs) to detail large-scale horizontal movements of deep water species: First results for the Greenland shark (Somniosus microcephalus). (April 2018) - Hussey, Nigel E.; Orr, Jack; Fisk, Aaron T.; Hedges, Kevin J.; Ferguson, Steven H.; Barkley, Amanda N.
Abstract: The deep-sea is increasingly viewed as a lucrative environment for the growth of resource extraction industries. To date, our ability to study deep-sea species lags behind that of those inhabiting the photic zone limiting scientific data available for management. In particular, knowledge of horizontal movements is restricted to two locations; capture and recapture, with no temporal information on absolute animal locations between endpoints. To elucidate the horizontal movements of a large deep-sea fish, a novel tagging approach was adopted using the smallest available prototype satellite tag – the mark-report pop-up archival tag (mrPAT). Five Greenland sharks ( Somniosus microcephalus ) were equipped with multiple mrPATs as well as a standard archival satellite tag (miniPAT) that were programmed to release in sequence at 8–10 day intervals. The performance of the mrPATs was quantified. The tagging approach provided multiple locations per individual and revealed a previously unknown directed migration of Greenland sharks from the Canadian high Arctic to Northwest Greenland. All tags reported locations, however, the accuracy and time from expected release were variable among tags (average time to an accurate location from expected release = 30.8 h, range: 4.9–227.6 h). Average mrPAT drift rate estimated from best quality messages (LQ1, 2, 3) was 0.37 ± 0.09 m/s indicating tags were on average 41.1 ± 63.4 km (range: 6.5–303.1 km) from the location of the animal when they transmitted. mrPATs provided daily temperature values that were highly correlated among tags and with the miniPAT (70.8% of tag pairs were significant). In contrast, daily tilt sensor data were variable among tags on the same animal (12.5% of tag pairs were significant). Tracking large-scale movements of deep-sea fish has historically been limited by the remote environment they inhabit. The current study provides a new approach to document reliable coarse scale horizontal movements to understand migrations, stock structure and habitat use of large species. Opportunities to apply mrPATs to understand the movements of medium size fish, marine mammals and to validate retrospective movement modeling approaches based on archival data are presented. Highlights: Currently complex to track horizontal movements of deep water species. Prototype mrPATs, the smallest available satellite tag, were tested to address this question. Horizontal tracks were derived through sequential releases of multiple mrPATs per shark. The experimental design revealed a timed migration of sharks from Canada to northwest Greenland. mrPATs can be used to understand the movements of large/medium size fish and marine mammals. mrPATs can validate retrospective movement models using archival depth/temperature data.